THE EFFECT OF TRUST, RISK, AND WEB DESIGN ON CONSUMER INTENTION BY MEANS OF CONSUMER ATTITUDE TO PURCHASE ONLINE - Putra, Bayu Anugerah Perdana Wijaya; Rochman, Fatchur; Noermijati, Noermijati (Universitas Brawijaya, Indonesia, 2017)
This study analyzed the effect of trust, risk, web design and its relation with consumer attitude and consumer intention to buy online in Malang. Population in this study are society of Malang and the number of the sample is 120 respondents. The sampling techniques is purposive sampling and the data is analyzed with parsial least square (PLS) analysis. The results indicate several findings that trust, risk, web design and consumer attitude have direct effect on consumer intention to buy online. Web design have an efffect on consumer intention to buy online through consumer attitude. But not with trust and risk, because trust and risk does not have significant effect on consumer intention to buy online through consumer attitude.